2019
DOI: 10.1063/1.5131703
|View full text |Cite
|
Sign up to set email alerts
|

Decoration of plasmonic Mg nanoparticles by partial galvanic replacement

Abstract: This is a repository copy of Decoration of plasmonic Mg nanoparticles by partial galvanic replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 49 publications
0
46
0
Order By: Relevance
“…In this case, the procedure of fabrication was based on a galvanic replacement reaction (GRR). , With respect to chemical dealloying, the GRR enables one to prepare almost oxygen-free porous films, and recently, this method is more and more explored. For example, Asselin et al reported on the decoration of Mg nanoparticles to improve their plasmonic properties, and Liu et al reported on chirality transfer in NPMs during GRR …”
Section: Nanoporous Metals For Enhanced Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the procedure of fabrication was based on a galvanic replacement reaction (GRR). , With respect to chemical dealloying, the GRR enables one to prepare almost oxygen-free porous films, and recently, this method is more and more explored. For example, Asselin et al reported on the decoration of Mg nanoparticles to improve their plasmonic properties, and Liu et al reported on chirality transfer in NPMs during GRR …”
Section: Nanoporous Metals For Enhanced Spectroscopymentioning
confidence: 99%
“…10,51 With respect to chemical dealloying, the GRR enables one to prepare almost oxygen-free porous films, and recently, this method is more and more explored. For example, Asselin et al 158 reported on the decoration of Mg nanoparticles to improve their plasmonic properties, and Liu et al reported on chirality transfer in NPMs during GRR. 159 It is extremely challenging to prepare nanoporous Al by means of chemical dealloying.…”
Section: Nanoporous Metals For Enhanced Spectroscopymentioning
confidence: 99%
“…(g–l) SEM images of GR products of Mg NPs by Au for different Au equivalents, all on the same scale as shown in (i). Adapted with permission from ref . Copyright 2019 AIP Publishing.…”
Section: Resultsmentioning
confidence: 99%
“…6 The electrochemical reactivity of colloidal Mg -using its strong reducing potential as driving force -leads to rapid galvanic replacement with other metals, such that Mg can be used either as a sacrificial template 7 or a scaffold for partial replacement leading to multifunctional, multimetallic architectures. 8 While Mg's reactivity can be utilised for syntheses, it renders Mg 0 intrinsically unstable in a number of common conditions. Indeed, metallic Mg tends to oxidize spontaneously to form a thin layer of MgO when in contact with air and Mg(OH) 2 when in contact with water.…”
Section: Introductionmentioning
confidence: 99%
“… 6 The electrochemical reactivity of colloidal Mg – using its strong reducing potential as driving force – leads to rapid galvanic replacement with other metals, such that Mg can be used either as a sacrificial template 7 or a scaffold for partial replacement leading to multifunctional, multimetallic architectures. 8 …”
Section: Introductionmentioning
confidence: 99%